2020
DOI: 10.1038/s41467-020-18824-8
|View full text |Cite
|
Sign up to set email alerts
|

Orbital climate variability on the northeastern Tibetan Plateau across the Eocene–Oligocene transition

Abstract: The first major build-up of Antarctic glaciation occurred in two consecutive stages across the Eocene–Oligocene transition (EOT): the EOT-1 cooling event at ~34.1–33.9 Ma and the Oi-1 glaciation event at ~33.8–33.6 Ma. Detailed orbital-scale terrestrial environmental responses to these events remain poorly known. Here we present magnetic and geochemical climate records from the northeastern Tibetan Plateau margin that are dated precisely from ~35.5 to 31 Ma by combined magneto- and astro-chronology. These reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 75 publications
(213 reference statements)
2
34
0
Order By: Relevance
“…The Late Oligocene red mudstone sequence from the Duitinggou section has a stratigraphic thickness of 105 m. It is highly expanded, contains no stratification, and has a homogeneous red color ( Fig. 1C ), which all indicate a stable deposition condition in a distal alluvial environment ( 21 , 23 , 24 ). The red color is consistent with frequent subaerial exposure leading to pedogenesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Late Oligocene red mudstone sequence from the Duitinggou section has a stratigraphic thickness of 105 m. It is highly expanded, contains no stratification, and has a homogeneous red color ( Fig. 1C ), which all indicate a stable deposition condition in a distal alluvial environment ( 21 , 23 , 24 ). The red color is consistent with frequent subaerial exposure leading to pedogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…1, B and C ), spans a (near-) continuous time interval between 28.1 and 24.1 Ma BP ( 15 , 16 , 18 , 19 ). Here, we use elemental and environmental magnetic records from this terrestrial sequence, which are related to regional hydroclimate fluctuations in the Lanzhou Basin ( 20 , 21 ), to provide insight to orbital variability and dynamics of monsoon precipitation on the NE Tibetan Plateau margin in the Late Oligocene high CO 2 world. Our results represent the first ~4-thousand year (ka) resolution Late Oligocene monsoon records from the Tibetan Plateau and thereby help fill a gap in our understanding of the orbital Asian monsoon variability and forcing dynamics in a unipolar icehouse state.…”
Section: Introductionmentioning
confidence: 99%
“…As the largest arid region in the temperate zone, central Asia is currently home to approximately one tenth of the global population. In the Paleogene, a “planetary” subtropical arid zonal pattern dominated in this region (Figures 1a and 1b; Guo et al., 2008; T. Liu et al., 1998), and an arid climate has been formed since the Cenozoic via stepwise aridification and desertification, which have been affected by the growth of the Tibetan Plateau (Guo et al., 2002, 2008; Miao et al., 2012; Ramstein et al., 1997), progressive retreat of the Paratethys Sea (Bosboom et al., 2011; R. E. Bosboom et al., 2014), and/or long‐term global cooling (Ao et al., 2020; Dupont‐Nivet et al., 2007; Fang et al., 2015; Fang, Galy, et al., 2019; J. X. Li et al., 2018). The Tibetan Plateau has blocked moisture sourced from the south and has driven atmospheric subsidence on the leeward side, resulting in drying of the NE Tibetan Plateau through the Cenozoic (An et al., 2001; Guo et al., 2002; Sato, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The most of previous studies based on marine sediments suggested that the climate change would be connected with the decline of atmospheric carbon dioxide (CO 2 ) concentration, the switch of ocean current system and the variation of the solar radiation (Coxall et al, 2005;Goldner et al, 2014;Liu et al, 2018;Gallagher et al, 2020). On the other hand, some studies of lacustrine records are not well consistent with marine records and suggested that there was a significant climate cooling with obviously seasonal climate change, and the regional aridification in the middle and high latitude continental areas, while some other studies suggested minor or insignificant climate changes (Stephen et al, 2005;Dupont-Nivet et al, 2007;Pei et al, 2007;Eldrett et al, 2009;Hren et al, 2013;Fang et al, 2019;Ao et al, 2020). Obviously, the systematic research on more terrigenous records, especially the records of the low latitude lacustrine sediments, is much needed to the full understanding of the climate change in the late Paleogene.…”
Section: Introductionmentioning
confidence: 99%